Antioxidant Effects of Lutein in Neonatal Period - Tei, Monica; De Bernardo, Giuseppe; Bazzini, Francesco; Santacroce, Antonino; Belvisi, Elisa; Riccitelli, Marina; Bracciali, Carlotta; Buonocore, Giuseppe; Perrone, Serafina; on behalf of the “Gruppo di Studio di Biochimica Clinica Neonatale della Società Italiana di Neonatologia” (Journal of Pediatric Biochemistry, 2016)
During fetal life, a right balance between oxidants and antioxidants is required for survival and growth of the fetus. At birth, an overproduction of free radicals (FRs) together with poor antioxidant defenses may be detrimental for developing organs and tissues. Protecting the newborn infant against perinatal oxidative stress (OS) is a health care priority, and therefore the search for new, safe, and efficacious antioxidants has been a major quest during the last decade. Due to its antioxidant and anti-inflammatory properties, lutein, a compound belonging to the xanthophyll family of carotenoids, is one of the most promising molecules with clinical application during neonatal age. Lutein is not synthesized by humans, hence the intake primarily depends on diet. In the neonatal period, fresh human milk is the main source of lutein, though lutein-enriched infant formulas are now available. Oral supplementation represents an alternative source of lutein, and it has been demonstrated to decrease plasma biomarkers of OS and increase antioxidant capacity in the first days of life.
Keywords: oxidative stress; free radicals; reactive oxygen species; lutein